Professionalism and image laundry in the ICT age: a study of Nigerian librarians (2012)
This study investigated professionalism and image laundry in the ICT age of librarians in Nigeria with a view to encourage librarians to make more positive effort at becoming more relevant in society, give them the right perception their profession and proffer solution (s) that will properly launder the present image of the library profession in Nigeria. The survey design of research was adopted for the study and the simple random sampling technique was used in choosing the study population. The instruments for collecting data were the structured questionnaire, interview and focus group discussion. 350 copies of the questionnaire were administered to respondents while 336 were found valid for the study. The descriptive statistical method of analysis using mean and standard deviation was employed for data analysis. The study revealed that many Nigerian librarians were never interested in the profession before going in to study the course. Rather they studied librarianship because it was their last resort. Others studied Library Science because they were told to start with it, at entry and change to a better course later. The study recommended among other things that librarians should break out of the stereotype their predecessors left them, be proud of their profession and vigorously engage in self development thereby gaining new knowledge and imbibing current trends.